Antioxidant potential, antimicrobial activity, polyphenol profile analysis, and cytotoxicity against breast cancer cell lines of hydro-ethanolic extracts of leaves of (Ficus carica L.) from Eastern Morocco - Tikent, Aziz; Laaraj, Salah; Bouddine, Toufik; Chebaibi, Mohamed; Bouhrim, Mohamed; Elfazazi, Kaoutar; Alqahtani, Ali S.; Noman, Omar M.; Hajji, Lhoussain; Rhazi, Larbi; Elamrani, Ahmed; Addi, Mohamed (Frontiers in Chemistry, 2024)
Introduction Many beneficial compounds found in fig leaves can be used in tea and medicine. These compounds aid with digestion, reduce inflammation, and treat diabetes and bronchitis. Chetoui, Malha, Ghoudane, and Onk Hmam fig leaf hydro-ethanol extracts from Eastern Morocco were analyzed for metabolites and biological activities. Methods, results, and discussion: HPLC-UV examination revealed that the leaf extract included mainly caffeine, rutin, and ferrulic acid. Spectrophometric results show that Malha leaf is rich in polyphenols (62.6 ± 1.3 mg GAE/g) and flavonoids (26.2 ± 0.1 mg QE/g). Chetoui leaf contains the highest vitamin C content (8.2 ± 0.1 mg Asc A/100 g DW), while Onk Hmam leaf has the highest condensed tannin (4.9 ± 0.1 mg CatE/g). The investigations found that all leaf extracts were antioxidant-rich, with strong Pearson bivariate correlation between bioactive polyphenol levels and antioxidant tests for DPPH, β-carotene, ABTS, and TAC (values of −0.93, −0.94, −0.85, and 0.98, respectively). The coefficients for flavonoid content were −0.89, −0.89, −0.97, and 0.80, respectively. Disk diffusion and MIC results show that the hydro-ethanol fig leaf extracts eliminate fungi and bacteria. In addition, these fig leaf extracts showed promise cytotoxicity against the breast cancer cell lines MCF-7, MDA-MB-231, and MDA-MB-436 and an interesting selectivity index. In silico leaf bioactive component analysis revealed that myricitin inhibited NADPH oxidase the greatest (gscore −6.59 Kcal/mol). Trans-ferulic acid inhibits Escherichia coli beta-ketoacyl-[acyl carrier protein] synthase (−6.55 kcal/mol), whereas quercetin inhibits Staphylococcus aureus nucleoside diphosphate kinase (−8.99). CYP51 from Candida albicans is best treated with kaempferol and myricitin. Both had a glide gscore of −7.84 kcal/mol. Rutin has the most potent Sespace 3 anticancer activity, with a glide gscore of −7.09 kcal/mol. Conclusion This research indicates that fig leaf extracts from the region can be used in medicine, food, natural cosmetics, and breast cancer prevention. To maximize the value of these leaves, their use must be carefully studied. Naturally, this fortunate tree’s diversity must be preserved and enhanced.